HUBUNGAN DANA BOK DAN MOTIVASI DENGAN KINERJA PETUGAS KIA - Raisha Octavariny; Sermi Iyana Swita Sinaga (Jurnal Penelitian Kesmasy, 2018)
Purpose BOK is to review assist local government to implement health care Appropriate Minimum Service Standards (MSS) Health to review Accelerate the achievement of the MDGs WITH improve costs kos health center, village health post (Poskedes) and Integrated Service Post (Posyandu) hearts organizing health services , To run the program needs a strong motivation For KIA officer. Number wherewith Research husband is WITH THE observational cross-sectional design carried out in October 2015. A sample of 48 Namely orangutan KIA officer working in the region Pematangsiantar City Health Department. Data collection using a questionnaire distributed To the respondents. Data analysis was conducted WITH THE chi-square test significance level of 95%. Results of the analysis we found the majority of officers KIA motivation and low performance that is 50% and 52.1%, p value = 0.035, which means there is a connection with the performance of funds BOK KIA officer and p value = 0.002 which means that there is a relationship of motivation with performance KIA BOK paid-up funds and Motivation MAY affect the boarding costs so that the KIA Officer Program has been drafted Posted community health centers can run properly Subscription with sufficient funds and Motivation Officer Yang High so that there can be KIA issue is resolved.